Analyzing the Gender Gap in Digital Financial Services Access - Dwi Andayani; Muhtarom Muhtarom; Bonar Napitupulu (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2026)
This study examines the persistent gender disparity in digital financial inclusion, where Digital Financial Services (DFS) offer transformative opportunities but remain unevenly accessed by men and women. The background reveals that despite the rapid expansion of Fintech ecosystems and increased global adoption of digital financial tools, women continue to experience lower ownership and usage of digital accounts. The object of this research is to analyze the structural and social determinants contributing to the gender gap in DFS access and utilization. The proposed method adopts a mixed-methods approach, integrating quantitative analysis of global financial inclusion datasets with qualitative case studies of policies and programs explicitly designed to support women’s financial participation. The result indicates that digital literacy limitations, entrenched socio-cultural expectations, and restricted access to essential resources such as mobile devices, financial assets, and formal identification continue to reinforce systemic barriers preventing women from fully benefiting from digital finance advancements. The conclusion highlights that addressing this inequality requires gender-intentional strategies, inclusive design principles, and evidence-based policy intervention to ensure that DFS evolves not only as a technological innovation but also as an equitable instrument for financial empowerment and social inclusion.